A study on the factors that affect student's academic performance at UiTM Kota Bharu / Muhammad Nadzmi Abdul Ghani, Muhammad Syafiq Abd Rahman and Mohamad Syahmie Ibrahim - Abdul Ghani, Muhammad Nadzmi; Abd Rahman, Muhammad Syafiq; Ibrahim, Mohamad Syahmie (2018)
Academic performance is one of important factors that has been debated among educators in Malaysia is which measured through the scores in final examination of each semester. On top of that, the most reliable and proper way to gauge the undergraduates' performance in Malaysia was by using the Grade Point Average (GPA) grading format (Sean et al., 2015). It acts as one of the priority for undergraduates to lead them to a bright future next. Most of undergraduates nowadays remain unemployed and it was stated by Balakrishnan (2017) in his reports, that Malaysia Employer Federation (MEF) said that one of four graduated students stayed unemployed for about six months before be employed. Related to the problem, a study had been done to identify which variables between Self-efficacy, Motivation and Leaming strategy that mostly contributed to the students' academic performance which was measured through their grade point average (GPA) at the current semester. The population of the study involved were around 757 students in UiTM Kota Bharu and then the questionnaires were distributed to the 290 students and collected back around 276. Since Raosoft software indicated that was 256 students required as minimum sample, then 276 of sets of questionnaires were collected were considered as fulfilled to represent the total of population. Based on one of the objectives of the study, the result revealed that was no mean difference in GP A between genders but difference between courses existed. In addition, the next objective was to check whether the three factors might significantly affected the student's GPA and the result showed that it was only Motivation that significantly affected the GP A even both three were showed to have a weak positive correlation toward GP A based on the Multiple Linear Regression (MLR) method performed. For recommendation, educational institutions were urged to implement more motivational programs to motivate them and enhancing their GP A. Moreover, it was recommended to discover new factors that may contribute to the student's academic performance in order to increase the precision of the outcomes.